Testing the Use of Crowdsourced Information: Case Study of Bike-Share Infrastructure Planning in Cincinnati, Ohio - Afzalan, Nader (2017)
Considering the power of web-based tools for crowdsourcing, planning organizations are increasingly using these technologies to gather ideas and preferences from the public. These technologies often generate substantial, unstructured data about public needs. However, our understanding of the use of crowdsourced information in planning is still limited. Focusing on the City of Cincinnati Bike-share planning as a case study, this article explores the challenges and considerations of using crowdsourced information. Employing mixed analysis methods, the article analyzes participant suggestions and examines whether and how those suggestions were incorporated into the bike-share plan. Interpretive analysis of interviews provided insights about suggestions that were used in the final plan. The results highlight organizational opportunities and limitations. A variety of organizational factors affected the utility of crowdsourced information in Cincinnati bike-share plan. These include the capability of the planning organizations to analyze data and facilitate participation, and the perception of planners about the value of crowdsourced information and local knowledge.